2019
DOI: 10.1155/2019/2903920
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of EBM Process Parameters on Porosity and Microstructure of Ti-5Al-5Mo-5V-1Cr-1Fe Alloy

Abstract: In this article, the authors discuss the results of studies into the processing of Ti-5Al-5Mo-5V-1Cr-1Fe near-β titanium alloy (Ti-55511) by electron beam melting (EBM), an additive manufacturing technique. Due to its high flexibility in shaping mechanical properties, Ti-55511 alloy is commonly used in aircraft components such as landing gear or airframes. In this study, Ti-55511 powder was used and its properties were described as regards chemical composition and particle size distribution in order to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Such similarity can be explained by the similar α + β microstructure observed in both types of alloys after the EBM process. The microhardness of the EBM build sample seemed to slightly lower (but same in standard deviation) than what Kurzynowski et al [13] reported for EBM build Ti55511, previously.…”
Section: Microstructures Of the Build Materialssupporting
confidence: 46%
“…Such similarity can be explained by the similar α + β microstructure observed in both types of alloys after the EBM process. The microhardness of the EBM build sample seemed to slightly lower (but same in standard deviation) than what Kurzynowski et al [13] reported for EBM build Ti55511, previously.…”
Section: Microstructures Of the Build Materialssupporting
confidence: 46%
“…Liu et al [42] prepared a porous β-type Ti-24Nb-4Zr-8Sn with 70% porosity using EBM and found that a lower scanning speed results in more input energy; thereby, the produced struts with higher yield strength and fewer flaws. Kurzynowski et al [178] discussed the effect of the EBM process parameters on the porosity and microstructure of Ti-5Al-5Mo-5V-1Cr-1Fe alloy and pointed out that the maximum hardness is obtained at the energy input of 30 J/mm 3 and the scanning speed of 1800 mm/s. In addition, the Al content in Ti-5Al-5Mo-5V-1Cr-1Fe alloy is related to the scanning speed adopted.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…, indicating pore defects dominate the upper surface roughness. Among them, orange peel is the result of discontinuity of melted track due to the high scan velocity [22] . Figure 4 shows that the upper surface roughness by the four manufacturing strategies is similar, i.e., is approximately 4 μm.…”
Section: Fig 1: Flow Charts Of Four Types Of Manufacturing Strategiesmentioning
confidence: 99%